Hubungan Air Bersih, Jamban Sehat, CTPS dan Pengetahuan dengan Kejadian Diare pada Anak Usia 1 - 4 Tahun di Kecamatan Mempawah Timur Kabupaten Mempawah - Dwi Aswanti; Gusti Zakaria Anshari; Fathmawati Fathmawati (Jurnal Sehat Mandiri, 2024)
Diarrhea in East Mempawah has increased in the last four years. Data from 2017 to 2021 shows an increase of 76% in diarrhea cases. This study aims to determine the relationship between using clean water, healthy latrines, washing hands,and knowledge on preventing diarrhea in six villages and two sub-districts in East Mempawah. This study was a case-control study that observed 43 cases and 43 controls aged 1-4 years old children with research instruments in the form of questionnaires. Data analysis used the chi-square test. The results showed that clean water sources were not related to the incidence of diarrhea with a p-value = 0.065, OR = 2.376 (95% CI=0.9361-6.0309). Defecation behavior was not related to the incidence of diarrhea with p-value=0.88, OR=1.222 (95% CI=0.459-3.255). The habit of handwashing was the incidence of diarrhea with a p-value = 0.023, OR = 5.161 (95% CI=1.339-19.895). Knowledge was related to the incidence of diarrhea with p-value = 0.003, OR=2.877 (95% CI=1.194-6.934).This study concludes that there is a relationship between handwashing and knowledge of the incidence of diarrhea.The handwashing habit is related to the incidence of diarrhea due to low awareness and willingness to do it. The Health Service needs to hold joint cross-sector and cross-program socialization activities about the importance of handwashing,as well as provide handwashing facilities in public places so that people can easily access them.